Acute and chronic effects of drop-set training: A meta-analysis and systematic review - Havers, T.; Micke, F.; Geisler, S.; Held, S. (Sports Medicine - Open, 2026)
Background Drop-set training (DROP) is a time-efficient resistance training method for hypertrophy and strength. Its long-term adaptations remain debated, particularly in relation to its acute physiological responses such as metabolic stress and fatigue. This meta-analysis examines both acute and chronic effects of DROP to provide a comprehensive evaluation of its efficacy.